Methods for comparative migration law: insights from the social sciences. (27th January 2023) - Cope, Kevin L.
The nascent field of comparative migration law can do more than classify different approaches to migration law; it is well-positioned to address important open questions about law's impact on migrants, migration, and citizens. It can also help us better understand how and why countries enact certain immigration laws. To do so, researchers must draw on methods from the disciplines that have long studied migration institutions both comparatively and empirically. These social sciences offer particularly fertile grounds for methodological borrowing, given the well-developed data and empirical literatures that have emerged over the past few decades to better understand the causes and effects of migration, and the causal inference 'credibility revolution'. Researchers should also consider the insights developed in comparative law generally about the appropriate objects of comparison. Such an interdisciplinary marriage of methods could allow researchers to tackle a series of new and emerging questions on the causes-and-effects of migration law.